Prevention of Sexual Violence and Tract Infection Reproduction Through Information Communication Activitieseducation to Youth in City Disaster Risk Area Padang in 2020 - Yusefni, Elda; Hayati, Neni Fitra; Rustam, Yefrida (POLTEKKES KEMENKES PADANG, 2023)
Indonesia is an area prone to various disasters, according to the 2018 BNPB, the most dominant hydrometeorological disasters such as 605 tornadoes, 506 floods, 353 forests, and land fires, 319 landslides, 55 volcanic eruptions, 33 tidal waves and abrasion, 1 tsunami. The impact is greater especially on vulnerable groups such as women and children, including adolescents. The most frequent impacts experienced by adolescents are sexual violence and harassment such as rape, personal hygiene disorders, the risk of contracting STIs, and trafficking. The purpose of this study was to determine the effectiveness of IEC in preventing the incidence of violence and ISR among adolescents in disaster-affected areas in 2020. This type of research is a quasi-experimental, one-group pre and post-test research design. This research was conducted at the Midwifery Department of Padang. The study was conducted from September to November 2020. The population of this study was students of 1 d3 Midwifery in Padang. Sampling by consecutive sampling, totaling 92 people. Manual data processing and univariate data processing with frequency distribution, bivariate analysis with Mc Nemar. The results showed that the number of incidents of sexual violence/harassment before and after IEC was 6.5% and 4.3%, respectively. The incidence of ISR before and after IEC was 12% and 7.6%, respectively. Adolescent readiness before and after Information Education Comunication was 47.8% and 72.8%. The results of statistical tests before and after IEC on the incidence of sexual violence/harassment with p- value > 0.500. The results of statistical tests before and after IEC on the incidence of ISR with p-value > 0.125. The conclusion of this study is the effectiveness of IEC on the prevention of sexual violence and the incidence of ISR there is no difference before and after IEC. It is suggested to the local government to increase activities to prepare for disasters such as socialization, simulation, provision of adequate infrastructure for youth so that disaster risks to health and safety can be minimized.